Research Trend of Artificial Intelligence Application in Mathematics Education (International Journal of Scientific Research and Management (IJSRM), 2025)
Technology plays an important role in mathematics education around the world. Artificial intelligence (AI) is one of the products of technology that is widely used in academic activities, which is also accompanied by many studies examining the use of Artificial intelligence in mathematics education. This paper aims to look at the research trends on AI in mathematics education. The Systematic Literature Review (SLR) method was used to review 35 articles from internationally reputable journals obtained from Scopus. The article search process used keywords namely AI, Artificial Intelligence, and mathematics education. The findings showed a sharp spike in the publication of AI articles in 2024, especially on chatbots. Chatbots have become the focus of AI research in mathematics education and are mostly conducted at the college level with student subjects. The application of AI in mathematics education is characterized by the function of AI to realize personalized learning. Finally, this paper recommends that future research should increase the diversity of research related to AI in mathematics education, especially among teachers and students at various levels given that students today can easily access AI. Debriefing on maintaining academic ethics is also needed to avoid misuse of AI in mathematics education.